2012
DOI: 10.1002/pssb.201200349
|View full text |Cite
|
Sign up to set email alerts
|

Low‐temperature encapsulation of coronene in carbon nanotubes

Abstract: Coronene was encapsulated in single-walled carbon nanotubes (SWNT) by vapor-phase filling at high (450 8C) and low (385 8C) temperature and by nanoextraction from supercritical carbon dioxide. The presence of coronene inside the tubes was demonstrated indirectly via the formation of double-walled nanotubes (DWNT). To this end several subsequent annealing steps were applied and monitored by Raman spectroscopy. Our results show that the encapsulation is successful with all three methods. However, high-temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 14 publications
2
18
1
1
Order By: Relevance
“…[38] The geometrical effect of argon for the encapsulation of molecules into SWNTs demonstrated in our study is likely to be found for other gases as well and may possibly lead to the synthesis of new materials by using reactions of molecules in a space not only confined by the walls of the nanotube but also by the pressure of various gases. However, our experiments revealed that filling nanotubes under an atmosphere of argon gas provides rather different conditions for encapsulation of planar molecules and results in different kinds of products if the molecules react with each other inside the nanotubes.…”
Section: Resultssupporting
confidence: 53%
“…[38] The geometrical effect of argon for the encapsulation of molecules into SWNTs demonstrated in our study is likely to be found for other gases as well and may possibly lead to the synthesis of new materials by using reactions of molecules in a space not only confined by the walls of the nanotube but also by the pressure of various gases. However, our experiments revealed that filling nanotubes under an atmosphere of argon gas provides rather different conditions for encapsulation of planar molecules and results in different kinds of products if the molecules react with each other inside the nanotubes.…”
Section: Resultssupporting
confidence: 53%
“…Pea pod-derived DWNTs and TWNTs have specific advantages and disadvantages over the DWNTs and TWNTs grown by the arc-discharge method and the CVD method [104,120,130,131,[134][135][136][137][138][139][140][141][142]150]. One advantage is that the method of growing the multi-walled structures by thermally-treating pea pods makes it possible to obtain high-purity CNTs without contaminants, such as metallic impurities.…”
Section: Pea Pod-derived Method: Advantages and Disadvantagesmentioning
confidence: 99%
“…This happens because the electronic structure of the constituent inner tubes is predominantly determined by the outer tubes, as well as by the high temperature observed during the thermal treatment. It is very interesting to note that the interlayer spacing in pea pod-derived structures strongly depends on the high temperatures achieved during the thermal treatment [104,120,130,131,[134][135][136][137][138][139][140][141][142]150].…”
Section: Pea Pod-derived Method: Advantages and Disadvantagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interest in an important PAH, namely coronene, also known as superbenzene stems from the fact that it has an intense structured fluorescence in the green region of visible spectrum that makes it a good candidate for excellent fluorescent molecular probe as revealed in several studies (10,11).Due to its high molecular symmetry (D 6h ), coronene has been favorite for spectroscopic studies. Coronene was encapsulated in the single walled carbon nanotubes for the production of coronene filled carbon nanotube (12). A few members of coronene family were investigated in supramolecular electronics and its one derivative was found to form excellent carbon nanotube with interesting electrical properties (13).…”
Section: Introductionmentioning
confidence: 99%